Effect of humic acid on nutrient content and uptake by mustard (Brassica juncea L.) - SV Wadekar,; AL Jat,; YR Patel,; ML Meena, (Journal of Oilseed Brassica, 2025)
An experiment was conducted in the rabi season of 2023-24 at the Agronomy Instructional Farm, Chimanbhai Patel College of Agriculture, Sardarkrushinagar Dantiwada Agricultural University, Sardarkrushinagar, India. The soil of experimental field is loamy sand in texture, a neutral pH, low organic carbon and available nitrogen; and medium levels of available phosphorus, potash, and sulphur. The experiment was conducted in randomized block design with three replications. In which, sixteen treatment combinations were tested, consisting of four levels of soil application of humic acid (S0 : 0 kg/ha, S1 : 10 kg/ha, S2 : 20 kg/ha, S3 : 30 kg/ha) and four levels of foliar spray of humic acid [F0 : control (water spray), F1 : 20 ppm, F2 : 40 ppm, F3 : 60 ppm]. The results revealed that significantly higher seed yield (1740 kg/ha), stover yield (4359 kg/ha), K content in seed (0.725%) and stover (1.404%), higher NPKS uptake by crop and K2O status after harvest in soil (255.7 kg/ha) recorded with soil application of humic acid @ 30 kg/ha. Foliar spray of  humic acid (60 ppm) secured significantly (mentioned level of significance) higher seed yield (1694 kg/ha), stover yield (4299 kg/ha) and NPKS uptake.